Strategi Perumusan Misi Jasa Pendidikan Di Era Digital - Ratih Fatonah; Mahfud Ifendi (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
Education is a human necessity and vital to the progress of a country, always undergoing change, development, and improvement following development in all areas of life. This article aims to describe the efforts of Lions Geweh Nursing SMK in formulating relevant and effective missions. The main objective of this article is to provide a comprehensive overview of how schools face challenges, innovate in learning approaches, and use social media to introduce themselves to the community. This research uses the techniques of qualitative analysis as demonstrated by Miles and Huberman: data collection, data reduction, data presentation, and the drawing of conclusions. The conclusion of this article shows that the Digital Age Education Services Mission Formulation Strategy of South Geweh Lion Nursing SMK Successfully integrated technology into the curriculum and established a strong partnership with the health industry. The head of the school is committed to continuously improving the quality of education by providing specialized training for teachers and striving to ensure the relevance of the curriculum to the needs of the health industry. He hopes that Southern Geweh Lion Nursing SMK will become a responsive, relevant educational institution and produce competent graduates in the health world, competing at the national and global levels. And cooperation with the health industry is expanding ahead. Continuously increasing school presence on social media includes expansion to other platforms like Facebook, increased awareness, and student participation.